Как Маша нянчила воронят: сказки / Галина Лебедева; художник А. Шахгелдян - Лебедева Галина (Сказки для детей, 2008)
Экземпляры: ф. 24 (20091208) / Инвентарный номер: 44548 / Цена: 45.00 / Авт.знак: Л 33 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6